1986
DOI: 10.1111/j.1600-0714.1986.tb00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus Type 2 DNA in oral verrucous carcinoma

Abstract: Tissues from patients with oral verrucous carcinoma were examined for the presence of human papillomavirus (HPV). The tissues were stained for the presence of the type common papillomavirus antigen by immunohistochemical staining and the presence of HPV DNA was determined by in situ hybridization with biotin‐labelled HPV DNA probes. Seventeen tissue specimens were obtained from 9 patients, and included pre‐malignant lesions and primary and recurrent tumors. One pre‐malignant lesion was positive for papillomavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…Oral cancer biopsies have also been shown, in some cases, to contain HPV sequences, de Villiers et al (1985) and Adler-Storthz et al (1986b) detected HPV-2 DNA in oral squamous and verrucous carcinomas, and DNAs of HPV-16 (de Villiers et al, 1985;Maitland et al, 1987) and HPV-18 (Syrjanen et al, 1988) have been reported in other oral squamous celt carcinomas. Additionally, Maitland et al (1987Maitland et al ( , 1989 found that a large proportion of normal oral mucosal samples, as well as carcinomas, exclusively contain HPV-16 sequences, which in most cases varied from the prototype virus in their PstI restriction pattern.…”
mentioning
confidence: 97%
“…Oral cancer biopsies have also been shown, in some cases, to contain HPV sequences, de Villiers et al (1985) and Adler-Storthz et al (1986b) detected HPV-2 DNA in oral squamous and verrucous carcinomas, and DNAs of HPV-16 (de Villiers et al, 1985;Maitland et al, 1987) and HPV-18 (Syrjanen et al, 1988) have been reported in other oral squamous celt carcinomas. Additionally, Maitland et al (1987Maitland et al ( , 1989 found that a large proportion of normal oral mucosal samples, as well as carcinomas, exclusively contain HPV-16 sequences, which in most cases varied from the prototype virus in their PstI restriction pattern.…”
mentioning
confidence: 97%
“…Each site has premalignant lesions which progress from mild dysplasia to carcinoma in situ and invasive carcinoma. Reports regarding the presence of HPV genotypes within oral tumors by molecular hybridi zation techniques do appear in the literature [59][60][61]; however, the findings are not conclusive.…”
Section: Other Anogenital Cancers Related To Hpvmentioning
confidence: 98%
“…30 This system allows the typing of both high-risk HPV (types 16,18,26,30,31,33,35,39,45, 51, 52, 56, 58, 59, 66, 68, 70,73, 82i and 82m) and low-risk HPV (6,11,34,40,42,43,44,54,55,57,61,64,71,72,81 and CP6108).…”
Section: Hpv Dna Detection and Typingmentioning
confidence: 99%
“…42 For verrucous carcinoma arising from the head and neck region, it has been reported that high-risk HPV are opportunistic viruses enhancing other carcinogenic factors such as tobacco or alcohol. 43,44 In case of low-risk HPV types, sequence variations increasing their transforming potential has been described. 26 Moreover, it has also been suggested that malignant transformation may be more related to the host response to the HPV infections than to the virus itself.…”
Section: Human Papillomavirus In Verrucous Carcinomamentioning
confidence: 99%